Interactive region of interest scalability for wavelet based scalable video coder - Karunakar, A. K.; Manohara Pai, M. M. (Journal of real-time image processing, 2011)
The current wavelet-based scalable video coder supports quality, spatial and temporal scalabilities required for recent multimedia applications. One of the key scalability required by the Joint Video Team (JVT) is Interactive Region of Interest (IROI) scalability. This paper proposes a technique to interactively extract ROI from scalable sub bit-streams. At the encoder, after sub-band decomposition the 3D wavelet tree is divided into N sub tree, each of these has spatial relevance in the original video, which can be decoded interactively. A generalized model for optimal value of N is proposed, that satisfies minimum requirement of the JVT about IROI support at reduced cost of the encoder. The ROI request from decoder along with resolution and bandwidth are mapped to that in the sub-band domain and respective sub-bit-streams are identified. The extractor assigns more bandwidth to ROI and remaining to non-ROI regions. Hence the decoder reconstructs the video with highest quality at the ROI. The proposed IROI functionality enhances the scalability of video coding by additional dimension.